2018
DOI: 10.1001/jamaophthalmol.2018.2797
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Visual Deficits in Children With Developmental Dyslexia

Abstract: IMPORTANCE Developmental dyslexia (DD) is a specific learning disability of neurobiological origin whose core cognitive deficit is widely believed to involve language (phonological) processing. Although reading is also a visual task, the potential role of vision in DD has been controversial, and little is known about the integrity of visual function in individuals with DD. OBJECTIVE To assess the frequency of visual deficits (specifically vergence, accommodation, and ocular motor tracking) in children with DD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
60
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 35 publications
8
60
1
1
Order By: Relevance
“…Children with developmental dyslexia in general show an increased prevalence of visual deficits including accommodative dysfunction, 21 and the prevalence of AI in children with learning difficulties was reported to be 26%. 22 Similarly, children with Down syndrome are found to have poorer accommodative amplitudes for their age, resulting in a high prevalence of AI ranging between 55% and 76%.…”
Section: Methodsmentioning
confidence: 99%
“…Children with developmental dyslexia in general show an increased prevalence of visual deficits including accommodative dysfunction, 21 and the prevalence of AI in children with learning difficulties was reported to be 26%. 22 Similarly, children with Down syndrome are found to have poorer accommodative amplitudes for their age, resulting in a high prevalence of AI ranging between 55% and 76%.…”
Section: Methodsmentioning
confidence: 99%
“…Both subtests are also a good indication of the level of academic performance 5 , 13 , 14 , reading rate 6 , 15 17 , and speed of visual processing 10 . Additionally, children with dyslexia perform worse than typically developing readers 18 . For these reasons, the horizontal and vertical DEM can still be useful in clinical settings when a quick assessment of visual functioning is required 10 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Dyslexia is a developmental learning disorder that emerges in childhood. The primary deficit involves problems with word recognition, decoding words, and spelling, which translates into slower reading, decreased comprehension, and even difficulty writing 1 , 2 . Though it is a prevalent condition, it is often difficult to describe a clear pathologic presentation of the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Though traditionally dyslexia has been described as a behavioral issue, there have also been studies that have shown that dyslexics do have physiologic deficits as well: they demonstrate evidence of abnormal visual processing, including abnormal saccadic and vergence eye movements, and visual rehabilitation has been recommended for decades to improve symptoms in dyslexic adolescents 1,[10][11][12][13][14][15] . Though dyslexia is considered a learning disability rooted in phonologic processing deficits, and though studies have shown physiologic problems in coordinating eye movements, there has been no longitudinal or randomized interventional trial that has demonstrated whether these physiologic problems are the consequence of poor reading and spell problems, or the cause of these issues.…”
mentioning
confidence: 99%